Experimental and Simulation Study of In-Cylinder Strategies For Regeneration of Lean Nitrogen Oxide Traps In A High-Speed Direct-Injection Diesel Engine - Koochak, Mostafa; Gharehghani, Ayatallah; Shahbakhti, Mahdi (SAGE Publications, 2013)
The use of lean nitrogen oxide traps is an attractive solution for reducing the tailpipe emissions of nitrogen oxides in vehicles with diesel engines. During the operation, nitrogen oxides are stored on the surfaces of lean nitrogen oxide traps, and regeneration of lean nitrogen oxide traps is required for proper operation. In this paper, two in-cylinder combustion strategies for regeneration of lean nitrogen oxide traps were assessed for a high-speed direct-injection diesel engine. In particular, a delayed and extended main strategy and a premixed compression ignition strategy were studied through experiments and simulations. The experimental data were collected from a 1.5 l diesel engine to analyze its combustion, exhaust temperature, fuel consumption, and emission characteristics resulting from either the delayed and extended main strategy or the premixed compression ignition strategy. The results indicated that the premixed compression ignition strategy offered a better fuel economy and lower soot and nitrogen oxide emissions, while the delayed and extended main strategy offered a hotter exhaust temperature and higher production rates of reductant species. In addition, a one-dimensional numerical lean nitrogen oxide trap model was designed and validated to study the efficiency of the surface adsorbents on lean nitrogen oxide traps for each of these two strategies in terms of a reduction in the nitrogen oxide emissions. The simulation results revealed that both strategies can reach a lean nitrogen oxide trap efficiency rate of 100% when the exhaust gas recirculation rate was equal to 30% but that the lean nitrogen oxide trap efficiency rate drops when lower exhaust gas recirculation rates were applied. Overall, the results indicated that the premixed compression ignition strategy performed better than the delayed and extended main strategy in terms of the fuel economy and lower tailpipe emissions.